Deceased Donor Uterus Transplantation: A Narrative Review of the First 24 Published Cases - Pecorino, Basilio; Scibilia, Giuseppe; Ferrara, Martina; Veroux, Pierfrancesco; Chiofalo, Benito; Scollo, Paolo (Medicina (Kaunas, Lithuania), 2024)
Uterus transplantation is the surgical treatment for absolute uterine factor infertility (AUFI), a congenital or acquired condition characterized by the absence of a uterus. More than 80 transplants have been performed worldwide, resulting in more than 30 live births, originating both from living and deceased donors. The collection of published articles on deceased donor uterus transplantations was performed in PubMed and SCOPUS by searching for the terms "Uterus transplantation" AND "deceased donor"; from the 107 articles obtained, only case reports and systematic reviews of deceased donor uterus transplantations and the resulting live births were considered for the present manuscript. The extracted data included the date of surgery (year), country, recipient (age and cause of AUFI) and donor (age and parity) details, outcome of recipient surgery (hysterectomy), and live births (date and gestational age). The search of peer-reviewed publications showed 24 deceased donor uterus transplantations and 12 live births (a birth rate of 66%) with a 25% occurrence of graft loss during follow-up (6 of 24). Among this series, twelve transplants were performed in the USA (seven births), five in the Czech Republic (one birth), three in Italy (one birth), two in Turkey (two births), and two in Brazil (one birth). The median recipient age was 29.8 years (range 21-36), while the median donor age was 36.1 years (range 20-57). Of 24 recipients, 100% were affected by MRKH (Mayer-Rokitanski-Kuster-Hauser) syndrome. Two live births were reported from nulliparous donors. Deceased donor uterus transplantation birth rates are very similar to the living donor rates reported in the literature, but ethical implications could be less important in the first group. It is necessary to register every case in the International Registry for Uterus Transplantation in order to perform a systematic review and comparison with living donor rates.
Keywords: Live Birth; těhotenství; Itálie; dárci tkání; Turkey; Humans; lidé; narození živého dítěte; Uterus; ženská infertilita; uterus; Turecko; Czech Republic; Congenital Abnormalities; Infertility, Female; Brazílie; Italy; Female; Mullerian Ducts; Adult; Tissue Donors; vrozené vady; 46, XX Disorders of Sex Development; ženské pohlaví; poruchy sexuálního vývoje s karyotypem 46, XX; ductus Mülleri; dospělí; Brazil; Česká republika; Pregnancy